Biomimetic Nanomedicine Coupled with Neoadjuvant Chemotherapy to Suppress Breast Cancer Metastasis via Tumor Microenvironment Remodeling. (29th March 2021) - Liu, Hai‐jun; Wang, Junfeng; Wang, Mingming; Wang, Yuzhen; Shi, Shanshan; Hu, Xiangxiang; Zhang, Quanguang; Fan, Daping; Xu, Peisheng
Abstract: The biomimetic enzyme activity of cerium oxide nanoparticles (CeNPs) prefers ultrasmall particle size and bare surface. Unfortunately, those two features are not favorable for its in vivo application due to easy aggregation and fast renal filtration. To take advantage of the activity of CeNP for cancer therapy, a homologous targeted cerium oxide nanoparticle system, targeted CeNP (T‐CeNP), with the integration of a biodegradable dendritic mesoporous silica nanoparticle, superoxide dismutase and catalase mimicking CeNPs, and the camouflage coating of cancer cell membrane has been developed. Attributed to the homologous targeting effect of cancer cell membrane, nanoparticles with camouflage coating are retained in the tumor in an orthotopic breast cancer metastatic model. Subsequently, T‐CeNP effectively hinders cancer‐associated fibroblast transdifferentiation and reprograms it back to a normal fibroblast. Consequently, T‐CeNP coupled with doxorubicin reduces the size of primary tumors and prevents the post‐surgery lung metastasis and liver metastasis of breast cancer. Abstract : A homologous targeted cerium oxide nanoparticle system (T‐CeNP) is developed for remodeling the tumor microenvironment by inhibiting cancer‐associated fibroblast transdifferentiation and reprogramming them back to normal fibroblasts. T‐CeNP coupled with doxorubicin reduces the size of the primary tumor and prevents post‐surgery lung metastasis and liver metastasis of cancer in an orthotopic breast cancer model.